SIMULASI KINEMATIKA MEKANISME LENGAN BACKHOE EXCAVATOR - Ginanjar Mustofa; Stenly Tangkuman; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
In the modern era as now required a fast and efficient calculation method which is usually done by simulation method. The software used in this simulation is SolidWorks 2016. SolidWorks is a parasolid based solid modeling, and uses a parametric-based approach to modeling and assembly. Parameters refer to restrictions that are valuable to determine shape or geometry of the model.               Based on this in this research will be kinematics simulation, where the result of simulation covering the whole workspace on excavator arm. The object research is a Backhoe Excavator arm mechanism of Hitachi ZX-type ZX-200. The purpose of this study was to determine velocity, tangential acceleration, and normal acceleration in excavator arm mechanism.               The maximum velocity of boom bar is 2948.82 mm/s which occurs when the boom angle is at 16.64° (t = 3.83s) or at the minimum angle of the workspace. The boom velocity simulation results have also been validated by hand calculation, maximum tangential acceleration is 2430.12 mm/s2, and the maximum normal acceleration is 3705.11 mm/s2. The maximum velocity of arm shaft is 1778.06 mm/s which occurs when the angle of arm rod is at 140.86°, maximum tangential acceleration is 4594.03 mm/s2, and the maximum normal acceleration is 6665.24 mm/s2. The maximum velocity of bucket rod is 473.61 mm/s, maximum tangential acceleration is 90.09 mm/s2, and maximum normal acceleration is 297.89 mm/s2. Keywords: Kinematic Analysis, Arm Excavator, Hitachi ZX-200.